ANALISIS TINGKAT KECACATAN DENGAN METODE SIX SIGMA PADA LINE TGSW: (ANALYSIS OF DEFECT LEVELS WITH SIX SIGMA METHOD IN LINE TGSW) - Nasrun Baldah (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2020)
This study aims to defect analysis on the TGSW line. Research data the monthly report period Mei 2018 to April 2018. By using the six sigma method for the T4N-Case Group type in the DMAIC concept and what factors cause defect T4N-Case Group product type. The resulting number of production from Mei 2018 to April 2019 amounted to 838.519 pcs with the number of defect products that occurred in production amounted to 2.106 pcs. Based on the calculation, the TGSW line is at a sigma level of 4,32 with the possibility of damage to the level of 3.401 for one million productions (DPMO). Abstrak Pada penelitian ini bertujuan untuk analisis defect pada line TGSW. Data yang digunakan dalam penelitian ini periode Mei 2018 sampai dengan April 2019. Dengan menggunakan metode six sigma untuk type T4N-Case Group dalam konsep DMAIC dan faktor-faktor apa saja yang menyebabkan terjadinya produk cacat pada type T4N-Case Group. Hasil penelitian jumlah produksi dari bulan Mei 2018 sampai bulan April 2019 adalah sebesar 838.519 pcs dengan jumlah produk cacat yang terjadi dalam produksi sebesar 2.106 pcs. Berdasarkan perhitungan, line TGSW berada pada tingkat sigma 4,32 dengan kemungkinan kerusakan sebasar 3.401 untuk sejuta produksi (DPMO).